2010
DOI: 10.1074/jbc.m110.118521
|View full text |Cite
|
Sign up to set email alerts
|

Type IIB Procollagen NH2-propeptide Induces Death of Tumor Cells via Interaction with Integrins αVβ3 and αVβ5

Abstract: Cartilage is resistant to tumor invasion. In the present study, we found that the NH 2 -propeptide of the cartilage-characteristic collagen, type IIB, PIIBNP, is capable of killing tumor cells. The NH 2 -propeptide is liberated into the extracellular matrix prior to deposition of the collagen fibrils. This peptide adheres to and kills cells from chondrosarcoma and cervical and breast cancer cell lines via the integrins ␣ v ␤ 5 and ␣ v ␤ 3 . Adhesion is abrogated by blocking with anti ␣ v ␤ 5 and ␣ v ␤ 3 antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…SPARC is a matricellular glycoprotein that is not only multifunctional, but is perhaps the only molecule here that has extensive reviews devoted to both its angiogenic (or tumourpromoting) and antiangiogenic (or tumourinhibiting) roles (Refs 172, 173, 174 194) that might have a role in keeping the cartilage avascular and could be exploited to kill tumours in vivo. The interaction of recombinant human PIIBNP (GST-PIIBNP) with hCh-1 cells (human chondrosarcoma cell line) was dependent on α V β 5 and α V β 3 integrins and took place in an RGDRGD-dependent manner in vitro.…”
Section: Secreted Protein Acidic and Rich In Cysteinementioning
confidence: 99%
“…SPARC is a matricellular glycoprotein that is not only multifunctional, but is perhaps the only molecule here that has extensive reviews devoted to both its angiogenic (or tumourpromoting) and antiangiogenic (or tumourinhibiting) roles (Refs 172, 173, 174 194) that might have a role in keeping the cartilage avascular and could be exploited to kill tumours in vivo. The interaction of recombinant human PIIBNP (GST-PIIBNP) with hCh-1 cells (human chondrosarcoma cell line) was dependent on α V β 5 and α V β 3 integrins and took place in an RGDRGD-dependent manner in vitro.…”
Section: Secreted Protein Acidic and Rich In Cysteinementioning
confidence: 99%
“…19 Moreover, the NH 2 -propeptide of the cartilage-characteristic collagen, such as type II B, PIIBNP, is released into the ECM prior to formation of the collagen fibrils, and when it is suppressed by small interfering RNA, adhesion is blocked. 20 Therefore, we chose the fragment (from 11 to 11036 bp) encoding the N-terminal of Col1a1 for antisense-mediated gene knockdown study.…”
Section: Discussionmentioning
confidence: 99%
“…These viscinal RGD's are conserved throughout mammalian species ( Figure 1A). Using recombinant PIIBNP and mutant PIIBNP (RGDRGD to RGARGA), we found that PIIBNP, but not mutPIIBNP was able to inhibit cell viability of a human chondrosarcoma cell line (hCh-1), a breast cancer cell line, MDA231, and HeLa cells (18). This inhibition was not dependent on the substrate supporting the cells indicating that the process was not simply anoikis in which the protein competes for integrin binding ( Figure 1B).…”
Section: Piibnp Is Anti-tumormentioning
confidence: 91%
“…This inhibition was not dependent on the substrate supporting the cells indicating that the process was not simply anoikis in which the protein competes for integrin binding ( Figure 1B). We found that the hCh-1 cells were actually being killed by a process of programmed cell necrosis (18). Studies using a mouse model of breast cancer tumor development demonstrated that in vivo, injected PIIBNP could inhibit the growth of tumors ( Figure 1C, 18).…”
Section: Piibnp Is Anti-tumormentioning
confidence: 96%
See 1 more Smart Citation